Impacts of three types of solar geoengineering on the Atlantic Meridional Overturning Circulation - Xie, Mengdie; Moore, John C.; Zhao, Liyun; Wolovick, Michael; Muri, Helene (Atmospheric Chemistry and Physics, 2022)
Climate models simulate lower rates of North Atlantic heat transport under greenhouse gas climates than at present due to a reduction in the strength of the Atlantic Meridional Overturning Circulation (AMOC). Solar geoengineering whereby surface temperatures are cooled by reduction of incoming shortwave radiation may be expected to ameliorate this effect. We investigate this using six Earth system models running scenarios from GeoMIP (Geoengineering Model Intercomparison Project) in the cases of (i) reduction in the solar constant, mimicking dimming of the sun; (ii) sulfate aerosol injection into the lower equatorial stratosphere; and (iii) brightening of the ocean regions, mimicking enhancing tropospheric cloud amounts. We find that despite across-model differences, AMOC decreases are attributable to reduced air–ocean temperature differences and reduced September Arctic sea ice extent, with no significant impact from changing surface winds or precipitation − evaporation. Reversing the surface freshening of the North Atlantic overturning regions caused by decreased summer sea ice sea helps to promote AMOC. When comparing the geoengineering types after normalizing them for the differences in top-of-atmosphere radiative forcing, we find that solar dimming is more effective than either marine cloud brightening or stratospheric aerosol injection.